Dukungan Keluarga dan Lama Dialisis Sebagai Faktor Berhubungan Dengan Kepatuhan Pembatasan Cairan Pasien Gagal Ginjal Kronik: Family Support and Dialysis Duration as Associated Factors Compliance with Fluid Restriction in Chronic Renal Failure Patients - Tiurmaida Simandalahi; Siska Sakti; Ropendi Pardede (NERS Jurnal Keperawatan, 2019)
Noncompliance with fluid restriction is a problem in patients undergoing hemodialysis. The impact suchs pulmonary edema increases the risk of cardiovascular disorders, and hypertension. This study aims to determine the relationship of family support and the length of dialysis with adherence to fluid restriction in patients with Chronic Renal Failure (CRF) in the RST. Reksodiwiryo Padang. This type of analytic descriptive research with cross-sectional design. Data collection was conducted in August 2018 in the RST hemodialysis unit room Dr. Reksowidiryo Padang. The population was all patients with CRF who underwent hemodialysis therapy with an average visit of 42 patients. Sampling by means of the total population. Data were collected using questionnaires and documentation studies, processed computerically. Univariate analysis with frequency distribution and bivariate with chi-square test significance of 0.05. The results showed that 76.2% were not adherent to limiting fluid, 52.4% did not get family support, 66.7% were in the old category of running dialysis. There was a significant relationship between family support (p = 0.030) and dialysis time (p = 0.001) with fluid restriction compliance. It was concluded that there was a relationship between family support and the length of dialysis with fluid restriction compliance. It is suggested to officers to include, educate, and motivate patients with their families regarding fluid restrictions, describe the impact, and give enthusiasm in carrying out dialysis therapy and provide alternatives that can be done for fluid replacement in controlling thirst.